Agricultural Modernization and Rural Development: Reference to Traditional Agriculture Transformation in Nepal - Shahi, Bhupendra Bahadur (Journal of Nepalese Management and Research, 2022)
This study has aimed to analyze the process of agricultural modernization and rural development in Nepal that focused on the issue, the contribution of agricultural growth and rural development in the case of agriculture modernization. It is qualitative in nature based on secondary literatures such as theory of agriculture modernization and some relevant literatures of Nepalese economy were reviewed to analyze the level of agriculture modernization of Nepal; agriculture has significantly contributed in its national economy as one of the dominant sectors; the sector found not being transformed even the numbers of policy measures implementing for its modernization. Still the most of the Nepalese people depends upon traditional agriculture sector as their major source of income, struggling in a adverse situation in this sector both in economic growth and farm productivity. In the context of agriculture modernization, the country has brought various policy measures and programs before and after establishing democracy in 1990.Various policies and programs aimed, Nepal would go through the process of agricultural transformation even though, and the result found to be remained the same. It is happening because of the policy gap in the process of formulation and implementation; still most of the Nepali farmers are engaged in the traditional agriculture that is subsistence. There is also found the situation of high ratio of unemployment, underemployment, seasonal unemployment and disguised unemployment in the country. Thus, the country Nepal has probably found to be failing in the process of agriculture modernization and the ratio of economic growth contribution in the gross national economy has gradually been decreasing instead of being radical increase from a decade 2011 to 2021.